Uncovering Implicit Assumptions: Reviewing the Work–Family Interface in Family Business and Offering Opportunities for Future Research. (March 2020) - Michael-Tsabari, Nava; Houshmand, Marjan; Strike, Vanessa M.; Efrat Treister, Dorit
The work–family interface (WFI) in family businesses (FBs) is an underrecognized area of research. The permeable nature of the boundaries in FBs between work and family is often treated as self-evident and as preventing (rather than inviting) research. We review the WFI in FBs based on 72 published articles and highlight implicit assumptions that have given rise to gaps in this literature. We show how boundary theory, the work–home resources model and the resource-based view can be used to highlight issues related to ownership, work–family enrichment, and contextual factors at the individual, family, and firm domains.